EVALUATION OF HERBICIDES FOR WEED CONTROL EFFICACY IN GROUNDNUTS (ARACHIS HYPOGAEA L.) IN THE GUINEA SAVANNAH ZONE OF GHANA - Dzomeku, I. K. (UDS International Journal of Development, 2017)
Groundnut (Arachis hypogaea L.) is the most popular leguminous crop cultivated for food and cash in the Guinea savannah zone of Ghana. A field experiment was conducted to study the effect of pre-emergence and post emergence herbicides for weed control in groundnuts during the 2011 and 2012 cropping seasons. The study determined the most suitable combination of herbicide with or without hand weeding that could enhance efficient weed control and promote yield and yield components in groundnuts. Thirteen weed control treatments were laid out in randomized complete block design with four replications. Percent mean weed index, which determines the reduction in crop yield due to the presence of weeds and an ideal parameter to judge treatment weed control effectiveness, was least with the application of: pendimenthalin at 0.15kg a.i./ha plus one hand weeding at 4WAP, haloxyfop at 0.03kg a.i./ha plus one hand weeding 7WAP, propaquizafop at 0.02kg a.i./ha at 4WAP plus one hand weeding at 7WAP and also bentazon at 0.14kg a.i./ha at 4WAP plus one hand weeding at 7WAP. The same treatments gave weed control efficiencies of 78 to 85% comparable to the accepted farmer control practice of twice weeding at 3 and 6 weeks after planting. Combination of pre- and post- emergence herbicides as a weed control package in groundnuts does not appear advantageous. Season-long weed infestation reduced pod yield by 36% in 2011 and 76% in 2012. Summed dominance ratio of weed species amplified prevalence of broadleaves such as Ageratum conyzoides (L), Commelina africana ( Linn), Corchorus olitorius (Linn), Hyptis suaveolens (Poit) and Ludwigia abyssinica (A. Rich). Season-long unweeded entries gave pod yield loss of 43 to 69%.Â  Keywords: Herbicides, Groundnut, Pod Yield, Weed Control Efficiency, Weed Index